CONSTRUINDO UM AVIÃO EM PLENO VOO: A INFLUÊNCIA DO CONFORTO FÍSICO NO CLIMA ORGANIZACIONAL DE UMA INSTITUIÇÃO FEDERAL DE ENSINO SUPERIOR - Denise Gutierrez Castro (Universidade Federal de Santa Catarina, 2017)
Driven by the Brazilian program Restructuring and Expansion of Federal UniversitiesBrazilian, the federal universities are placed in a setting that has booming,. With that in someunits the servers perform their activities on your desktop with unfinished physical facilitiesand construction. Whereas the physical comfort is one of the dimensions of organizationalclimate, this article aims to address how the physical environment influences the formation ofthe organizational climate construction. Therefore, this article ispresented with a qualitativeapproach to measure the phenomenon, obtained through an exploratory research. Data werecollected from the records of group discussions through participant observation. Theergonomics point of view, the employees of this institution are greatly affected due to thebuilding being under construction. The problems mentioned were: loud noises, problems ofhygiene and cleanliness, insecurity and tremors in the physical structure. It was found that theworkers demonstrated insecurityand concern for these work situations that consequentlyaffect the physical comfort, one of the organizational climate factors. However, it wasobserved that even with the difficulties evaluated, servers end up not fail to perform theirduties.